74.3k views
4 votes
Simplify this expression.

Simplify this expression.-example-1
User Kuru
by
5.5k points

2 Answers

3 votes

Answer:


(6w^2 y^4)/(x)

Explanation:


(12x^3 y^6 w^5)/(2x^4 y^2 w^3)


= (12w^5 x^3 y^6)/(2w^3 x^4 y^2)


= (12w^2 y^4)/(2x)


= (6w^2 y^4)/(x)

Hope this helped you!

User Jinnie
by
5.5k points
3 votes

Answer


\frac{ 6 {y}^(4) {w}^(2) }{{x}}

Step-by-step Explanation


\huge \frac{12 {x}^(3) {y}^(6) {w}^(5) }{ 2{x}^(4) {y}^(2) {w}^(3) } \\ \\ \huge= \frac{6 {x}^(3) {y}^(6) {w}^(5) }{{x}^(4) {y}^(2) {w}^(3) } \\ \\ \huge = 6 {x}^(3 - 4) {y}^(6 - 2) {w}^(5 - 3) \\ \\ \huge= 6 {x}^( - 1) {y}^(4) {w}^(2) \\ \\ \huge = \frac{ 6 {y}^(4) {w}^(2) }{{x}^(1)} \\ \\ \huge = \frac{ 6 {y}^(4) {w}^(2) }{{x}}

User Peter Wortmann
by
5.7k points